Liberdade de crença e política: tensões e controvérsias no campo religioso afro-brasileiro em São Paulo - Candido, Joel Valentino (2015)
This dissertation consists of survey the tensions in the religious afro-brazilian field in São Paulo, generated around the Project Law 992/2011 - authored by State Representative Feliciano Nahimy Filho, in progress the Legislative Assembly of São Paulo - whose purpose is to forbid the use and/or animal sacrifices in religious rituals in the state of São Paulo. It also points out the controversies in the religious, political and judicial field in which is inserted the above-mentioned Law Project, since it besides to be an attack the very religions of African roots, also harms the freedom of belief established in the Brazilian Federal Constitution. Among the religions with African roots, I shall take the Candomblé as a reference, for this religion be inserted in the context of the state representative s Law Project, since, in general, in their religious practices is present the animal sacrifice ritual. Starting interviews and academic contribution from several sciences of knowledge, it was possible to analyze that the tensions experienced by the Candomblé followers are relevant, because the proposition of this law is an attempt to avert the religious practice of a social group that, throughout History, has been object of discrimination, prejudice and racism